Strategi Pemasaran Yayasan Pondok Pesantren Baitul Huda Dengan Menggunakan Metode K-Means - Dudih Gustian; Aang Hasanudin (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The Baitul Huda Islamic Boarding School Foundation is a boarding school located in Sukabumi Regency, precisely in the Surade Jampang Kulon sub-district. Founded in 2021 by a graduate of the Annidzom Panjalu Sukabumi Islamic Boarding School Kyai Haji Abdul Rohim and is now being cared for by the founder's sons and daughters. Officially the Baitul Huda Islamic Boarding School Foundation manages the MI, MT and MA education levels. There are many Islamic boarding school facilities in Surade Jampang Kulon District, but for Islamic boarding school facilities around the Baitul Huda Islamic Boarding School Foundation, there are only four Islamic boarding school campuses. The problem in this research is the lack of a marketing strategy. The cause of the weakness of the marketing strategy is that it has not been widely socialized due to the lack of social media, so not everyone knows about it. This study uses Operations Research techniques with the K-Means method. This research provides a solution for the Baitul Huda Islamic Boarding School by creating a website as a publication media for the Islamic Boarding School.